Menelusuri Sistem Kuota Haji Di Indonesia: Perspektif Hukum Tentang Kesetaraan Ham Dan Transparansi (RechtJiva, 2025)
This research aims to explore the Hajj quota system in Indonesia from a legal perspective, focusing on issues of human rights equality and transparency in its determination. This research uses a normative juridical research method with a statutory approach and a case approach. The search for legal materials is carried out through literature study and literature inventory, with legal material analysis techniques including systematic interpretation and teleological interpretation. Based on the provisions of Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah, Indonesia's hajj quota is divided into regular quota and special hajj quota. However, in practice, the allocation of hajj quotas often generates controversy, especially in terms of unbalanced quota distribution and unclear procedures. This study examines the application of the law regarding the allocation of Hajj quotas, assesses whether the existing system fulfills the principle of equality for all prospective pilgrims, and whether there is transparency in the decision-making process by the Ministry of Religious Affairs.